Cybersecurity Awareness: A Literature Review on Internet Users' Awareness and Safe Behavior - Ananda Amalia Putri (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The rapid development of information technology has facilitated various aspects of human life, from communication and education to financial transactions. However, this progress has also been accompanied by the growing threat of cybercrime, such as data theft, hacking, and digital fraud. One of the most influential factors contributing to this growing threat is the low level of cybersecurity awareness among internet users. This article aims to review the various literature related to cybersecurity awareness and user safety behavior in the online world. The method used is to review literature from various scientific sources from 2022 to 2025 that discuss cybersecurity awareness, behavior, and education. The results of the study show that while security technology continues to evolve, human awareness remains the weakest point in cyber defense. Therefore, improving education and digital culture is a key strategy in developing safe behavior among internet users.